Effect of pendulous and erect pinna on population size and frequency of Malassezia globosa and Malassezia pachydermatis in external ear canal of healthy dogs - Lim, Jiehan; Arshad, Habibah (2010)
Forty clinically healthy stray dogs were used to determine the effect of type of pinna on the population size and frequency of Malassezia globosa and Malassezia pachydermatis in external ear canal of healthy dogs. Two methods were used: cytological examination and fungal culture. The prevalence of M. globosa were 25 and 40% in pendulous and erect pinna, respectively. Both pinna recorded a very low mean count of 0.03 yeast/hpf. However, no growth of colonies was seen on modified Dixon’s agar, therefore, M. globosa could not be confirmed. This study confirmed a high prevalence of M. pachydermatis in dogs with pendulous pinna (90%) which was higher than in dogs with erect pinna (65%). High population size of M. pachydermatis can be isolated from dogs with pendulous pinna (1074 cfu per swab) and dogs with erect pinna (466 cfu per swab) using fungal culture. There was a strong association of occurrence of otitis externa and type of pinna which predisposed dogs with pendulous pinna to be twenty-one times more at risk of developing otitis externa than dogs with erect pinna.